Evaluating the effectiveness of enhanced recovery after surgery protocols on outcomes in general surgery: a systematic review - Aljubouri, Salman A.; Alsaedi, Emad A.; Alrehaili, Meaad A.; Aloufi, Hussam K.; Alsubhi, Reham M.; Aljayyar, Mohammed W.; Seraj, Abdurrahman S.; Samman, Hasan M.; Alharbi, Amal N.; Kaki, Waleed K.; Mohammad, Heba A.; Alharbi, Nawaf H.; et al. (International Journal Of Community Medicine And Public Health, 2025)
Multimodal treatment pathways called enhanced recovery after surgery (ERAS) programs are intended to lessen surgery’s physical and emotional impacts. In many surgeries, patient outcomes are linked to better compliance with ERAS protocols. To investigate the effectiveness of ERAS protocols on outcomes in general surgery. The systematic review used PubMed, Scopus, Google Scholar, and Clinicaltrial.gov as data sources. Randomised clinical trials comparing any traditional protocol with ERAS. Protocols for general surgical procedures, published from January 2015 to January 2025, were included based on preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. A total of 1860 study titles were identified. Only randomised control trials were included, so 230 titles were produced as randomized controlled trial (RCT). Researchers chose 145 abstracts for screening after removing the papers that did not fit the original search criteria; only 13 qualified for final review. Three reviewers independently identified the relevant trials and extracted data on study details, outcomes, and efficacy from included studies. The overall hospital stay, pain score, medical cost, post-operative complications, morbidity, and inflammation were significantly reduced in the ERAS group (p<0.05), and improved quality of life, comfort level, and immunity. The study concluded that ERAS protocol helps to improve patient well-being after surgery and should be implemented in general surgery. Further longitudinal studies should also be conducted.